IMPLENTASI CSR TERHADAP KESEJAHTERAAN HIDUP MASYARAKAT - Joko Haryono; Abdul Wahid Mahsuni; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTThe purpose of this study is to know find out the influence CSR from PT.East Hope Agriculture towards the welfare of the villagers Bimo, pakuniran subdistrict, probolinggo district. Simultaneously and partially where the independentvariables are CSR Goal, CSI, CRP while the dependent variable is the welfare ofthe villager.case study of this study on the community of Pakuniran village, Pakuniransub-district, probolinggo district, where this type of research is casual associativeand the data used is using a questionnaire distributed as many as 277 respondentsusing a Likert scale. Data collection method uses purposive sampling method. Theanalytical tool used is multiple linear regression. the results of this study indicatethat corporate social responsibility goals, corporate social issues, corporaterelations programs simultaneously and partially have a significant effect on Thewelfare of people's lives analysis.KEY WORDS : Corporate Social Responsibility Goal, Corporate Social Issue,Corporate Relation Program and Community Welfare.